Effectiveness of Technologically Enhanced Peer Support in Improving Glycemic Management Among Predominantly African American, Low-Income Adults With Diabetes. Issue 3 (June 2019) - Heisler, Michele; Choi, Hwajung; Mase, Rebecca; Long, Judith A.; Reeves, Pamela J.
Purpose: The purpose of the study was to examine whether a peer coaching intervention is more effective in improving clinical outcomes in diabetes when enhanced with e-health educational tools than peer coaching alone. Methods: The effectiveness of peer coaches who used an individually tailored, interactive, web-based tool (iDecide) was compared with peer coaches with no access to the tool. Two hundred and ninety Veterans Affairs patients with A1C ≥8.0% received a 6-month intervention with an initial session with a fellow patient trained to be a peer coach, followed by weekly phone calls to discuss behavioral goals. Participants were randomized to coaches who used iDecide or coaches who used nontailored educational materials at the initial session. Outcomes were A1C (primary), blood pressure, and diabetes social support (secondary) at 6 and 12 months. Results: Two hundred and fifty-five participants (88%) completed 6-month and 237 (82%) 12-month follow-up. Ninety-eight percent were men, and 63% were African American. Participants in both groups improved A1C values (>–0.6%, P < .001) at 6 months and maintained these gains at 12-month follow-up ( >–0.5%, P < .005). Diabetes social support was improved at both 6 and 12 months ( P < .01). There were no changes in blood pressure. Conclusions: Clinical gains achieved through a volunteer peer coach program were not increased by the addition of a tailored e-health educational tool.